Konsentrasi Spasial Industri Besar Dan Sedang Di Provinsi Sumatera Selatan - Feby Rorencia; Bernadette Robiani; Deassy Apriani; Hamira Hamira (STIE Jambatan Bulan, 2024)
Industry is any type of economic activity that is responsible for managing a series of basic raw materials and also maximizing the potential results of the industrial sector so as to produce products that have added value or greater profits, including industrial services. The scope of this research is limited to large and medium industries located in the South Sumatra region. The purpose of this study is to measure the high and low spatial concentrations of large and medium industries that occur at the district and city levels in South Sumatra. The research method applied to test the spatial concentration of large and medium industries uses the Herfindahl Index (HHI) model, using labor data on large and medium industries from 2019 to 2021. The research results obtained show that the area in South Sumatra Province that has the highest spatial concentration of large and medium industries is in Palembang City, while South OKU Regency is the area that has the lowest spatial concentration of large and medium industries in South Sumatra Province.